Blood Management Strategies in Primary and Revision Total Knee Arthroplasty for Jehovah's Witness Patients - Issa, Kimona; Banerjee, Samik; Rifai, Aiman; Kapadia, Bhaveen H.; Harwin, Steven F.; McInerney, Vincent K.; Mont, Michael A. (The Journal of Knee Surgery, 2013)
Primary or revision total knee arthroplasties (TKAs) may be associated with a marked amount of intraoperative or postoperative blood loss that potentially may lead to the need for blood transfusions. However, Jehovah's Witnesses usually refuse blood transfusions because of their religious beliefs. This may create clinical or ethical challenges for the treating physicians. Therefore, following established blood management protocols specifically designed for these patients may be beneficial for the performance of safe and transfusion-free procedures with minimal complications. In this report, we provide an overview of various potential preoperative, intraoperative, and postoperative blood management measures that may be used for the care of Jehovah's Witnesses who undergo knee arthroplasty procedures. In addition, we review reported outcomes of primary and revision TKAs in these patients.
Keywords: total knee arthroplasty; blood management